The Influence of Good Corporate Governance and Enterprise Risk Management on Economic Performance with Corporate Ethical Identity as a Mediating Variable - Immami Immami; Iin Rosini; Ani Kusumaningsih (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study analyzes the relationship between Good Corporate Governance (GCG), Enterprise Risk Management (ERM), and Economic Performance, with Corporate Ethical Identity (CEI) as a mediating variable. The research sample consists of companies participating in the CGPI program from 2020 to 2023. Using a quantitative method with panel data regression analysis via EViews 13, the study finds that both GCG and ERM have a positive influence on the formation of CEI. However, GCG and ERM do not directly affect Economic Performance. Conversely, CEI is proven to have a positive and significant impact on Economic Performance. A key finding of this study is that CEI serves as a full mediator, meaning the influence of GCG and ERM on Economic Performance is entirely channeled through the strengthening of Corporate Ethical Identity.